The Presence of the Spirit in the Academy: Pentecostal and Charismatic Studies as an Interdisciplinary Concern - Vondey, Wolfgang (PentecoStudies, 2017)
The academic discipline of Pentecostal and Charismatic studies represents an interdisciplinary concern because the chief concern of Pentecostal and Charismatic movements is the presence of God's Spirit. This study pursues the modest goal to outline the contours of this interdisciplinarity by mapping the terrain of the recent renaissance of pneumatology with the emergence of Pentecostalism and its pursuit of the Spirit. The essay delineates the interdisciplinary character of the pursuit of the Spirit as an academic concern, offers a definition of Pentecostal and Charismatic Studies in terms of its pursuit of the Spiritual Presence, identifies boundaries and potential forms of this interdisciplinary discourse, and concludes by drafting a course towards a more fully interdisciplinary agenda.